DIFFERENTIAL DIAGNOSIS OF BRAIN GLIOMAS BY POSITRON EMISSION TOMOGRAPHY USING VARIOUS RADIOPHARMACEUTICALS - N. A. Kostenikov; L. A. Tyutin; N. P. Fadeev; A. F. Panfilenko; E. M. Zykov; Yu. R. Ilyushchenko; O. Yu. Makeeva (Вестник рентгенологии и радиологии)
Objective: to comparatively study the diagnostic capabilities of positron emission tomography (PET) with various tumorotropic radiopharmaceuticals (TRPs) in detecting malignant brain gliomas (BG) and estimating their degree.Material and methods. One hundred and fourteen patients, including 47 with histologically verified glioblastoma multiforme (GBM), 27 with anaplastic astrocytoma (AA), 23 with benign astrocytoma (BA), and 17 with postoperative cysts, were examined. PET was performed using TRPs: 18F-fluorodesoxyglucose (18F-FDG), 11C-sodium butyrate (11C-SB), 11C-L-methionine (11C-MET), and 11C-choline (11C-COL).Results. Malignant gliomas (GBM and AA) were clearly visualized by PET using 11C-MET, 11C-CHOL, and 11C-SB. 18F-FDG PET visualization of tumors was difficult because of increased RP accumulation in the cerebral cortex. WHO grades II–III gliomas were completely visualized by 11C-MET PET. Only some tumors were clearly displayed by PET with 11C-CHOL and 11C-SB. The accumulation indices (AI) obtained by 11C-CHOL PET in patients with malignant gliomas were, on average, 4.0- and 5.5-fold higher than those by 11C-MET and 11C-SB PET, respectively. Significant differences (p<0.001) in AI obtained by 11C-CHOL (11C-CHOL-AI) PET were first established between the patients with GBM (WHO grade IV) and those with AA (WHO grade III).Conclusion. 11C-CHOL PET is the most sensitive method to identify gliomas and estimate their grade. The advantage of 11C-MET PET is the possible imaging of the entire volume of viable tumor tissue.